운동치료, 심리치료 및 식이요법이 포함된 통합비만관리프로그램이 산업체에 근무하는 비만 환자의 체성분 및 혈액성분에 미치는 영향 - 서동권; Seo Dongkwon; 이병권; Lee Byoungkwon (Journal of the Korean Society of Integrative Medicine, 2019)
Purpose : The purpose of this study was to find out how changes in body shape of obese patients could be affected by the combined management of diet and psychotherapy along with exercise therapy to control energy imbalance, the cause of obesity. Methods : In this study, the aerobic exercise program was conducted on 12 industrial workers of “D” company for a total of eight weeks for obese patients with a high body mass index (25 ㎏/㎡ or higher). The experimental group did not apply the program three times a week. The body type analysis was carried out using the body analyzer (Inbody 770, Inbody, Korea) and blood test and psychological test were performed after 8 weeks of exercise before and after exercise Results : The results of the group showed a change in weight loss of 6.03 kg (p=.000) on average, which is nearly 10 % of the change in weight. It was also shown that the BMI (body mass index) decreased by 1.76 ㎏/㎡ (p=.000). Abdominal fat (AO) is also 0.14 % (p=.000), waist circumference (WC, 12.72 cm, p=.000), internal fat (VF, 25.12 %, p=.000), liver function levels AST (5.47 U/L, p=.04), ALT (13.64 U/L, p=.000), total cholesterol, pTC -14.22. Conclusion : Based on the results of this study, the obesity management program will be able to maximize the effects of obesity control if exercise programs and psychotherapy are combined.